Structure control for fine tuning fluorescence emission from side-chain azobenzene polymers - Smitha, P.; Asha, S. K. (Journal of Physical Chemistry B, 2007)
New fluorescent azobenzene dyes and side-chain polymers have been synthesized and characterized and their photophysical properties studied. A series of azobenzene dyes having different fluorophores such as phenol (S1), phenylphenol (S2) and naphthol (S3) incorporated in them were synthesized. S2 had unusually high fluorescence with a quantum yield of φf = 0.2 recorded in dichloromethane (DCM), whereas S1 and S3 were found to be weakly fluorescent. The azobenzene dyes were converted into methacrylate monomers having short ethyleneoxy spacers and then free radically polymerized. Phenylphenol-based azobenzene polymer (P2) continued to show fluorescence, whereas fluorescence was completely quenched in the case of phenol (P1)- and naphthol (P3)-based polymers. Phenylphenol, though twisted in the ground state is known to have a more planar geometry in the excited statea factor that enables it to retain its fluorescence behavior even when it is incorporated as part of an azobenzene unit. In contrast, naphthol, which is a better fluorophore compared to phenylphenol, loses much of its emissive behavior upon coupling to the azobenzene unit. The extent of trans to cis photoisomerization in solution was very low (∼17%) for P2 after 30 min of continuous irradiation using 365 nm light, in contrast to ∼ 40% for P1 under identical conditions. This is attributed to the steric repulsion brought about by the bulky phenylphenol units that restrict rotation. A 2-fold enhancement in fluorescence emission was observed for P2 upon irradiation by UV light at 360 nm, which relaxed to the original intensity in about 7 day's time. The higher emission of the cis azobenzenes is generally attributed to an inhibition of photoinduced electron transfer (PET) mechanism. The emission of P2 showed a concentration dependence which increased initially and then decreased in intensity with the formation of a new red-shifted peak at higher concentration due to aggregation. Irradiation of the fluorescence quenched highly concentrated (1 × 10-3 M) sample of P2 showed an enhancement in emission from aggregates at 532 nm.